Bio-solubilization of Yunnan lignite by Penicillium ortum MJ51 and characterization of its products. (1st January 2023) - Li, Shiying; Li, Fang; Li, Peipei; Wang, Yi; Shi, Qiuzhe; Liu, Xiaoqi; Tan, Jinfang; Han, Yanlai
Graphical abstract: Highlights: Strain MJ51 could solubilize 82.0% of pretreated lignite within 8 days. Multiple extracellular substances mediate the solubilization of lignite. Strain MJ51 can rebuild the intermolecular hydrogen bonding of lignite. Strain MJ51 can introduce C=O into the structure of coal in the same way as HNO3 . Black liquid fractions contained various aromatic and aliphatic compounds. Abstract: In this study, a newly discovered fungal strain Penicillium ortum MJ51 was isolated from lignite collected from a coal mine in Yunnan Province, China. The strain was then utilized to convert solid Yunnan lignite to liquid value-added chemicals. It solubilized 36.4% of the raw lignite and 82.0% of lignite pretreated with nitric acid within 8 days. The extracellular metabolites and enzymes secreted by MJ51 were detected dynamically, along with an analysis of the organic element composition, Fourier-transform infrared spectroscopy, and gas chromatography-mass spectrometry of the raw lignite, pretreated lignite, and their bio-solubilized residues and soluble fractions. The results suggested that extracellular metabolites including alkaline substances and surfactants, secreted by MJ51 were the primary contributors to the depolymerization of lignite, because the lignite-solubilization ability of MJ51 was correlated with pH and surface tension of the culture. Moreover, extracellular enzymes, such as lignin peroxidase and esterase, secreted by MJ51 participated in the degradation of lignite despite their poor activity. Furthermore, MJ51 could introduce CO into the structure of raw lignite in the same way as HNO3 . Under the associated action of extracellular alkaline substances, surfactants, and enzymes, the hydrogen bond in coal was rebuilt, the complex aromatic skeletons were opened, and the attached long aliphatic side chain was cut off. The pretreated lignite could be thoroughly degraded by MJ51 than raw lignite as it had a lower degree of aromatic condensation, shorter aliphatic side chain and more carbonyl groups. The soluble bio-solubilized fractions of lignite contained aliphatic and aromatic compounds, and their derivatives.